Effects of packaging and ripeness on plantain flour characteristics during storage. Issue 10 (7th July 2022) - Honfo, Fernande G.; Togbe, Euloge C.; Dekker, Matthijs; Akissoe, Noël
Abstract: The increasing implication of plantain flour in various food formulations calls for the need to evaluate the effects of ripening stage, packaging materials, and storage duration on its proximal composition and functional properties. For this study, plantain flours were produced from the cultivar Alloga at unripe and semiripe stage 3. They were stored both in transparent polyethylene bags and in an opaque aluminum foil. Physicochemical analyses and functional characterization of the plantain flour were performed on samples taken prior to storage and on monthly basis for 6 months during storage. Ash and carbohydrate contents decreased while the yellowness and redness increased with ripening. Pasting viscosity drastically decreased with ripening. During storage, significant differences in color and among most functional characteristics were observed as a consequence of both storage duration and packaging materials. Based on this research, flour from semiripe plantain could be recommended for use in formulations requiring low viscosity. Besides, it is suggested to store plantain flours in opaque containers to reduce the variability in its properties, thus maintaining its original quality. Abstract : The study investigated on the proximal composition and functional properties of flours derived from plantain at two ripening stages, and packaged in different materials during storage. Pasting viscosity drastically decreased with ripening. During storage, significant differences in color and among most functional characteristics were observed as a consequence of both storage conditions and packaging materials. However, variations were less pronounced in flours packaged in opaque materials.